The Impact of Sustainable Exercise on Self-Efficacy and Life Satisfaction in Women before and after Menopause - Abdulaziz Kulak; Turhan Toros; Emre Bulent Ogras; Ibrahim Efe Etiler; Emre Bagci; Belgin Gokyurek; Ulviye Bilgin (Behavioral Sciences, 2023)
The study aims at elucidating the association between sustainable exercise and its influence on self-efficacy and life satisfaction in women during their premenopausal and postmenopausal stages. A relational screening model was employed on a sample of 422 women, with 215 premenopausal and 207 postmenopausal participants, utilizing convenience sampling. Participants’ regularity of exercise and its duration was taken into consideration. Evaluation tools included the General Self-Efficacy Scale (GSES) and the Satisfaction with Life Scale (SWLS). Data were analyzed using a statistical software package with significance set at 0.05. Sustainable exercise demonstrated no significant difference in SWLS or GSES subdimensions among premenopausal women. However, postmenopausal women engaging in regular exercise reported significantly higher scores in SWLS and all GSES subdimensions. Moreover, positive correlations between age and SWLS scores, as well as between age and certain GSES subdimensions, were found in both pre- and postmenopausal periods. While sustainable exercise does not evidently impact the life satisfaction and self-efficacy of premenopausal women, it significantly enhances these parameters in postmenopausal women. Additionally, age appears to influence life satisfaction and specific self-efficacy subdimensions across both phases.